Dificuldades de leitura entre alunos do 3º ano do ensino fundamental da Escola Municipal Artur Reginaldo - BARBOSA, Cleidiane de Sousa (2019)
The work has as its theme: Difficulties of reading among students of the 3rd year of elementary school of the municipal school Artur Reginaldo. The theme is of paramount importance in the school context, especially in the first cycle of primary school literacy. The general objective of this research was to analyze the factors that contribute to the difficulties of reading acquisition of students of the 3rd year of elementary school at the Mun School. Ens. Inf. And Fund. Artur Reginaldo. The specific objectives were to know the process of reading acquisition in the 3rd grade classes; to identify learning difficulties in the reading of 3rd year students and to identify the factors that cause the reading learning difficulties of 3rd year students. The work was consolidated through the application of a semistructured interview with the students of the 3rd grade classes of the mentioned school, dialoguing with theoretical bases such as: Paulo Freire, Sonia Kramer, Emília Ferreiro, Ana Teberosky, among others. The results of this research point to a number of factors that contribute negatively to the acquisition of reading and writing in the students of the 3rd year of elementary school of the Regaldo Modesto School of Modesto, to the methodologies, instruments and spaces used for the literacy process of the students in the first cycle they present several deficiencies, because the literacy environment does not offer sufficient educational support to accompany the full development of the students, since according to the authors mentioned in the work, the teachers need to use diverse instruments to promote the learning of the reading and the writing, taking taking into account the learning needs of each student. However, it is worth mentioning that the difficulties of learning to read are a topic that is much discussed in the social sphere in the search for possible solutions to try to reduce a problem that is presented by a good part of Brazilian literacy students.